RETRACTED ARTICLE: Histological, ultrastructural, and biochemical study on the possible role of Panax ginseng in ameliorating liver injury induced by Lambda cyhalotherin - Manal Abdul-Hamid; Hanaa M. Mohamed; Sanaa M. Abd El-Twab; Karim Zaied (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Lambda-cyhalotherin (LCT) is a pyrithroid type 2 pesticide that is broadly utilized in pest control in public health, animal health, and agriculture. Although claiming that LCT has a low mammalian toxicity, several investigations reported its mammalian hepatotoxicity by mediating oxidative stress causes severe hepatotoxicity and liver damage. Results LCT significantly decreased catalase (CAT), superoxide dismutase (SOD), and total thiol (T. thiol) and increased lipid peroxidation (LPO). mRNA and protein expression levels of p53 were upregulated, whereas Bcl-2 mRNA and protein expression levels were downregulated in LCT-intoxicated animals. Also, light microscopic and ultrastructure studies for liver tissues of LCT-intoxicated animals showed mononuclear leukocytic infiltration in the parenchyma, congested portal vein with thickened wall, and proliferation of bile duct and hepatocytes with cytoplasmic vacuolations, fatty changes, and collagen fibers. Panax ginseng co-treatment attenuated oxidative stress biomarkers. Both tested doses of Panax ginseng (100 and 200 mg /kg b. wt./day) significantly decreased p53 and elevate Bcl-2 mRNA and protein expression levels and reveals significant amelioration and restoration of normal histology and ultrastructure of liver, but 200 mg/kg b. wt. of Panax ginseng seems to be more potent. Conclusion Panax ginseng exhibited ameliorative effect against hepatic oxidative stress, apoptosis, histopathological, and ultrastructural changes induced by LCT.